Direct and convenient measurement of plasmid stability in lab and clinical isolates of E. coli - Siyi Chen (Nature Portfolio, 2017)
Abstract Plasmids are important mobile elements in bacteria, contributing to evolution, virulence, and antibiotic resistance. Natural plasmids are generally large and maintained at low copy number and thus prone to be lost. Therefore, dedicated plasmid maintenance systems have evolved, leading to plasmid loss rates as low as 1 per 107 divisions. These low rates complicate studies of plasmid loss, as traditional techniques for measuring plasmid loss are laborious and not quantitative. To overcome these limitations, we leveraged a stringent negative selection system to develop a method for performing direct, quantitative measurements of plasmid loss in E. coli. We applied our method to gain mechanistic insights into a heterologously reconstituted segregation system in lab strains and clinical isolates of E. coli. We also performed direct stability studies of a currently circulating resistance plasmid in a clinical isolate, strain EC958, which is a member of the rapidly expanding global ST131 E. coli clone. Our results establish the foundational assays required to screen for small molecules targeting plasmid stability, which could complement current strategies for reducing the spread of antibiotic resistance, complementing other strategies for treating antibiotic resistant bacteria.